Innovative Commons-Based Management for Madagascar's Protected Areas - Ramasinoro Naly; Etienne Stefano Raherimalala; Sigrid Aubert; Andrianjary Myriam; Tsimiondrike Mahasoa; Ratiarimananjatovo Narindra; Koto-te-Nyiwa Ngbolua; Robijaona Rahelivololoniaina Baholy (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2024)
Faced with the rapid degradation of ecosystems, the ecological emergency is now undeniable according to global scientific analyses. In this context, protected areas, through shared governance, have emerged as one of the most effective strategies for preserving biodiversity and ultimately ensuring the survival of humanity. Madagascar, which has embraced this shared governance, relies on its local communities, the fokonolona, to ensure its effectiveness. However, these communities, living in precarious conditions, are heavily dependent on natural resources for their livelihoods and benefit little from the advantages of protected areas. Their adherence to the concept of protected areas remains uncertain. A field study revealed that while 52% support the concept of protected areas, 44% are not convinced. Nevertheless, since it is a state policy, all natural resource users have accepted it. One of the primary motivations for the fokonolona is the preservation of their cultural and natural heritage. They therefore advocate for joint co-management that guarantees their participation in inclusive local governance for their engagement in the protected area. 93% of respondents believe that this co-management should be conducted through a commons-based approach, which is well-rooted in their organization. Even other users, in order to defend their interests, aspire to this approach where all users define the rules for resource management themselves. However, this commons-based approach does not seem suitable for all categories of protected areas, including natural parks, which is the option chosen by the manager for Sahamalaza – Iles Radama.